Intellectual property: Linking patent granted and market capitalization to company performance / Nurul Huda Mohamad Amin - Mohamad Amin, Nurul Huda (2007)
This study investigates the relationship of patent granted to the company performance. Survey data from managers in the Intellectual Property Corporation (MylPO) will be used to conduct non-parametric test, which is Wilcoxon Matched- pairs signed Rank Test. The study used data from Main Board and Second Board from Bursa Malaysia Berhad and the company comprise from various sector. The variables include the market capitalization of 19 companies listed in Bursa Malaysia before and after they granted for the patent and the patent granted itself by that particular company. The study aims to examine whether the patent granted by MylPO has a significant relationship to the increasing in market capitalization and company performance listed in Malaysia. By analyzing the sample of 19 companies listed in Bursa Malaysia Berhad, it can be concluded that patent granted tend to reflect to the market capitalization of the company.